Bi‐band fresnel reflectarray for unmanned aerial system (UAS)‐satellite communication. Issue 5 (21st March 2016) - Ba, O.; Lanteri, J.; Migliaccio, C.; Menzel, W.
ABSTRACT: This article describes the design of a passive Bi‐band Fresnel reflectarray (20–30 GHz). It is focused on the design of the reflecting panel of the reflectarray. Two different primary feeds will be used at 20 and 30 GHz, respectively for demonstrating the proposed concept. Nevertheless, in the final design a switched primary feed will have to be used. The dual operation band is obtained with multiple resonant elementary cells. Although the paper deals with linearly polarized primary feed, an interesting property of these cells is that they also work with circular polarization. Moreover, a phase correction based on Fresnel zones is used in order to ensure the best tradeoff between simplicity and radiating performance. Finally, the reflecting panel is made and radiation pattern and gain measurements are shown. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:1025–1028, 2016